KEKERASAN DALAM RUMAH TANGGA (KDRT) TERHADAP ANAK DALAM PERSPEKTIF HAK ASASI MANUSIA (HAM) - SRYANI BR. GINTING; CHRISTINA NM., TOBING (JURNAL ILMIAH SIMANTEK, 2023)
Human rights in the perspective of the Indonesian Constitution have the spirit of Pancasila. Indonesia as a constitutional state implements the principles of the "Rule of Law" formally in the 1945 Constitution which includes, among other things, the protection of human rights in Chapter X A. “Kekerasan Dalam Rumah Tangga” (KDRT) is contrary with Precepts 2 of the Pancasila "Just and civilized humanity". In line with Article 28 G paragraph (2) of the 1945 Constitution, it is the constitutional basis for eliminating KDRT. The Human Rights Law, supported by the Law on the Elimination of KDRT and the Law on Child Protection, is a normative aspect that must be upheld for victims, namely children who are victims of KDRT. KDRT requires a comprehensive solution because it is complex and has an impact on the physical and mental suffering of victims. Raden Indrajana Sofiandi's domestic violence case is a form of human rights violation, especially the rights of children as victims. Considering that Indonesian children are the next generation of the nation, violations of children's human rights must be upheld fairly and correctly. Preventive efforts are carried out starting from home, awareness of law and human rights for parents and children and all those in the family environment need to be increased; repressive efforts through regulations/regulations and community collaboration, Komnas HAM together with law enforcers who have the spirit of Pancasila in order to carry out the mandate of the 1945 Constitution.